Exploring the roles of horizotnal gene transfer in metazoans - Chen, Dongliang (East Carolina University, 2016)
Horizontal gene transfer (HGT; also known as lateral gene transfer, LGT) refers to the movement of genetic information between distinct species by overcoming normal mating barriers. Historically HGT is only considered to be important in prokaryotes. Some researchers believe that eukaryotes have sexual recombination and HGT is insignificant. However, HGT has also been found to play roles in many aspects of eukaryotic evolution, like parasitism and the colonization of land by plants, although at lower frequencies than in prokaryotes. In this dissertation, I first estimated the scope of HGT in 16 selected metazoan species by genome screening using AlienG. These species are sampled to represent major lineages of metazoans. Among all the 16 species, Nematostella vectensis (4.08%) has the highest percentage of HGT genes, while parasitic Schistosoma japonicum (0.47%) ranks the lowest. In order to find out which factors are correlated with HGT rates in different species, living habitat, diet, lineage group and reproductive type were analyzed in a statistical framework. In Chapter 3 and Chapter 4, Ciona intestinalis and Trichoplax adhaerens were chosen as models to investigate horizontally acquired genes. Tunicate cellulose synthase was discovered to originate from green algae, instead from bacteria as found in previous studies. 43 genes of 21 families in T. adhaerens were found to be horizontally acquired. The functions and impacts of acquired genes on T. adhaerens are also discussed.
Keywords: Horizontal gene transfer; HGT; Genetic transformation; Metazoa; Prokaryotes; Eukaryotic cells--Genetics